Enhancing speaking performance and creativity using AI-Integrated learning tool in speaking classes - Hazwani, Hassim; Hafizoah, Kassim; Asiah, Kassim (Penerbit UMPSA, 2024)
This paper reports a small-scale study, which investigated the implementation of SpeechAce, an artificial intelligence (AI)-based platform, in English as a Second Language (ESL) classrooms at SM Sains Kota Tinggi (SAKTI), Johor, Malaysia. The research seeks to enhance students’ spoken English proficiency and overall performance by leveraging AI technology and addressing current educational challenges. The study involves 30 ESL learners, with data collected through pre- and post-intervention assessments, student questionnaires, and classroom observations. The findings revealed how AI-based platforms can provide personalized, real-time feedback, support autonomous learning, and foster active language use and creativity. The study is aligned with the goals of the Malaysian National Education Blueprint (2013-2025) and the CEFR framework, focusing on developing critical 21st-century skills, such as communication and creativity. By integrating AI tools, the research aims to provide practical recommendations for modernizing ESL instruction and enhancing students' performance and creative abilities in a rapidly evolving educational landscape.